Prion-like transmission of neuronal huntingtin aggregates to phagocytic glia in the Drosophila brain - Pearce, Margaret M.P. (Nat Commun, 2015)
The brain has a limited capacity to self-protect against protein aggregate-associated pathology, and mounting evidence supports a role for phagocytic glia in this process. We have established a Drosophila model to investigate the role of phagocytic glia in clearance of neuronal mutant huntingtin (Htt) aggregates associated with Huntington disease. We find that glia regulate steady-state numbers of Htt aggregates expressed in neurons through a clearance mechanism that requires the glial scavenger receptor Draper and downstream phagocytic machinery. Remarkably, some of these engulfed neuronal Htt aggregates effect prion-like conversion of soluble, wild-type Htt in the glial cytoplasm. We provide genetic evidence that this conversion depends strictly on the Draper signaling pathway, unveiling a previously unanticipated role for phagocytosis in transfer of pathogenic protein aggregates in an intact brain. These results suggest a potential mechanism by which phagocytic glia contribute to both protein aggregate-related neuroprotection and pathogenesis in neurodegenerative disease.